Prevalence and risk factors for abnormal tandem gait in patients with essential tremor syndrome: A cross-sectional study in Southwest China - Huang, Hongyan; He, Xianghua; Shen, Qiuyan; Zhang, Dan; Bao, Yi; Xu, Fang; Luo, Anling; Liu, Ling; Yang, Xinglong; Xu, Yanming (Frontiers in Neurology, 2023)
Objectives: Patients with essential tremor (ET) syndrome have more prevalent and more serious gait and balance impairments than healthy controls. In this cross-sectional study, we explored whether balance impairments are associated with falls as well as more pronounced non-motor symptoms in patients with ET syndrome. Methods: We assessed the tandem gait (TG) test, as well as falls or near-falls that occurred over the previous year. Non-motor symptoms—including cognitive deficits, psychological and sleep disorders—were evaluated. In univariate analyses, statistical significance was corrected for multiple comparisons using the Benjamini–Hochberg method. Multiple logistic regression was utilized to evaluate the risk factors for poor TG performance in patients with ET syndrome. Results: A total of 358 ET syndrome patients were divided into the abnormal TG (a-TG) and normal TG (n-TG) groups based on their performances in the TG test. We revealed that 47.2% of ET syndrome patients had a-TG. ET syndrome patients with a-TG were older, more common in females, more likely to present with cranial tremor and falls or near-falls (all adjusted P < 0.01). The a-TG patients had significantly lower Mini-Mental Status Examination scores, as well as significantly higher Hamilton Depression/Anxiety Rating Scale and Pittsburgh Sleep Quality Index scores. Multiple logistic regression analysis demonstrated that female sex (OR 1.913, 95% CI: 1.180-3.103), age (OR 1.050, 95% CI: 1.032-1.068), cranial tremor scores (OR 1.299, 95% CI: 1.095-1.542), a history of falls or near-falls (OR 2.952, 95% CI: 1.558-5.594), and the presence of depressive symptoms (OR 1.679, 95% CI: 1.034-2.726) were associated with the occurrence of a-TG in patients with ET syndrome. Conclusions: TG abnormalities may be a predictor of fall risk in ET syndrome patients and are associated with non-motor symptoms, especially depression.